Transverse Young's modulus of carbon/glass hybrid fiber composites. (March 2020) - Venkatesan, Ganesh; Ripepi, Maximilian J; Bakis, Charles E
Hybrid fiber composites offer designers a means of tailoring the stress–strain behavior of lightweight materials used in high-performance structures. While the longitudinal stress–strain behavior of unidirectional hybrid fiber composites has been thoroughly evaluated experimentally and analytically, relatively little information is available on the transverse behavior. The objective of the current investigation is to present data on the transverse modulus of elasticity of unidirectional composites with five different ratios of carbon and glass fiber and to compare the data with predictive and fitted models. The transverse modulus increases monotonically with the proportion of glass fiber in the composite. Finite element analysis was used to evaluate different ways to model voids in the matrix and allowed the unknown transverse properties of the carbon fibers to be backed out using experimental data from the all-carbon composite. The finite element results show that the transverse modulus can be accurately modeled if voids are modeled explicitly in the matrix region and if modulus is calculated based on stress applied along the minimum interfiber distance path between adjacent fibers arranged in a rectangular array. The transverse modulus was under-predicted by the iso-stress model and was well predicted by a modified iso-stress model and a modified Halpin–Tsai model.